A reflection about the linguistic-communicative competence and the proficiency of the (future) foreign language teacher in Brazil - Consolo, Douglas Altamiro (2018)
In this chapter I present a discussion about the language proficiency in foreign languages of foreign language (FL) teachers, with emphasis on contexts of teacher education in Brazil. The focus is on the reflection based on theoretical and empirical data that can support the definition of language aspects to be considered in the establishment of standards for such proficiency, which derives from those teachers’ linguistic-communicative competence. The issue of a linguistic-communicative competence of EFL teachers, as discussed by Consolo (1996, 1999, 2000b, 2002, 2004, 2005a,b) and Teixeira da Silva (2000), is dealt with here based on a theoretical background on language competence and proficiency (Bachman and Palmer, 1996; Elder, 2001; Llurda, 2000, Scaramucci, 2000, to name a few). A description of FL teachers’ linguistic-communicative competence can impact on the construct for FL assessment of teachers, as well as a typology of language that should be managed by those (future) teachers in the Brazilian context and elsewhere.